The Application Concept of Social Capital Theory and Social Exchange Theory: The Comparisson of Collaboration and Networking Strategy in Knowledge Obtaining in Indonesia and China - Darmasetiawan, Noviaty Kresna (Department of Management, Faculty of Economics and Business, Brawijaya University, 2013)
The originality of this research is to apply the grand theory of social capital and social exchange theory to a discussion of the strategy of collaboration and networking among companies in knowledge obtaining on companies in Indonesia and China. The comparison between the two countries is based on the perspective of institutional theory and culture paradigm, whereby the firms in both countries have a specific difference. This research resulted in the proposition that (1) Organizational trust is a variable that affects the strategy of collaboration and networking for knowledge obtaining between firms, (2) There is collaboration and networking for knowledge obtaining between companies in Indonesia and China, (3) there are differences in terms of organizational trust collaboration and networking for knowledge obtaining between companies in Indonesia and China. Limitations of this study are, this is the study with limited to an assessment and conceptual literature excavation that remains to be proved further by research in the field.Â